Aku Mampu Bertahan: Peran Dukungan Sosial dan Spiritualitas Meningkatkan Resiliensi pada Dewasa Awal - Alfin Lintang Eldzani; Raissa Dwifandra Putri (Fakultas of Psychology, Universitas Muria Kudus, 2025)
Resilience is one of the important qualities that individuals in early adulthood need to possess, especially when facing various challenges and uncertainties in life. This study aims to examine the role of spirituality and social support in enhancing resilience among early adults. Using a quantitative approach, involved 292 participants selected through convenience sampling. All participants were Indonesian citizens aged 18-30 years. Data were collected using questionnaires consisting of the Multidimensional Scale of Perceived Social Support (MPSS), the Attitudes Related to Spirituality Scale (ARES), and the Adult Resilience Measure-Revised (ARM-R). Data analysis was conducted using multiple linear regression. The results of the study indicate that spirituality and social support collectively contribute to increased resilience (p < 0.001), with a combined contribution of 75,5%. Furthermore, partial regression analysis shows that both spirituality and social support individually contribute to resilience, with social support contributing 39,9% and spirituality contributing 35,6%. This study confirms that individual resilience is influenced by a combination of internal and external factors, namely spirituality as an internal factor and social support as an external protective factor. This research enriches the study of resilience in early adulthood by highlighting the synergy between psychosocial factors and spirituality within the Indonesian cultural context. Resiliensi merupakan salah satu hal penting yang perlu dimiliki individu di dewasa awal yang tengah mengalami berbagai tantangan serta ketidakpastian dalam hidup. Penelitian ini bertujuan untuk menguji peran spiritualitas dan dukungan sosial dalam meningkatkan resiliensi pada individu dewasa awal. Melalui pendekatan kuantitatif, penelitian ini melibatkan 282 partisipan yang dipilih melalui teknik convenience sampling. Seluruh partisipan merupakan Warga Negara Indonesia (WNI) dengan rentang usia 18-30 tahun. Data dikumpulkan menggunakan kuesioner yang terdiri dari The Multidimensional Scale of Perceived Social Support (MPSS), Attitudes Related to Spirituality Scale (ARES), dan Adult Resilience Measure-Revised (ARM-R). Analisis data dilakukan menggunakan regresi linear berganda. Hasil penelitian menunjukkan bahwa spiritualitas dan dukungan sosial berkontribusi secara bersama-sama terhadap peningkatan resiliensi (p < 0,001), dengan kontribusi sebesar 75,5%. Selain itu, analisis regresi secara parsial menunjukkan bahwa spiritualitas dan dukungan sosial juga berkontribusi dalam peningkatan resiliensi, dengan kontribusi sebesar 39,9% untuk dukungan sosial dan 35,6% untuk spiritualitas. Penelitian ini memberikan penegasan bahwa resiliensi individu dipengaruhi oleh kombinasi faktor internal dan eksternal, yaitu spiritualitas sebagai sumber daya psikologis internal dan dukungan sosial sebagai faktor protektif eksternal. Secara ilmiah, penelitian ini memperkaya kajian resiliensi pada dewasa awal dengan menyoroti sinergi antara faktor psikososial dan spiritualitas dalam budaya Indonesia.